Novel rotor retaining sleeves for air conditioning systems in aircrafts. (Research'eu results magazine)
'Air conditioning systems' (ACSs) used in aircraft applications need to provide sustainable energy benefits and better performance. An EU initiative aimed to improve ACSs to meet these requirements.